Analisis Kandungan Gizi Protein dan Kalsium pada Susu Kacang Almond Sebagai Alternatif Pengganti Susu Sapi - Syukrina, Fatma; Febrianti, Kamila Dwi; Djannah, Roichatul (Nindikayla Institute, 2024)
Background: Cow's milk is a widely consumed source of protein and calcium, but it cannot be consumed by individuals with lactose intolerance or a cow's milk protein allergy. Plant-based milks, particularly almond milk, have the potential to be an alternative because they are lactose- and casein-free and contain essential nutrients.Objective: This study aimed to analyze the protein and calcium content of almond milk with varying compositions as an alternative to cow's milk.Methods: This study was an experimental study with a completely randomized, one-factor design. Treatment variations were based on differences in the proportions of raw materials. Protein content was analyzed using the Bradford method, while calcium content was analyzed using the complexometric method. Data were analyzed using a one-way ANOVA test with a 95% confidence level.Results: Almond milk is a plant-based milk product obtained from processed almonds and is known to have high nutritional content and provide various health benefits. This beverage is becoming increasingly popular because many people cannot consume cow's milk due to allergies to cow's milk protein or lactose intolerance. Thus, almond milk is an alternative to cow's milk and a plant-based milk option other than soy milk for individuals with animal lactose intolerance. To assess the quality of almond milk, tests were conducted on the essential mineral content for the body, namely calcium (Ca) and iron (Fe), in commercial almond milk beverage products on a household scale consisting of samples A, B, and C. The milk samples were prepared using a 65% nitric acid solution, then diluted before being analyzed for mineral content. The test results showed that all samples contained calcium and iron minerals. The average calcium levels in samples A, B, and C were 114.92 ppm, 166.07 ppm, and 163.80 ppm, respectively, with the highest levels in sample B and the lowest in sample A. Meanwhile, the average iron levels in samples A, B, and C were 3.78 ppm, 3.42 ppm, and 2.44 ppm, respectively, with the highest iron content in sample A and the lowest in sample C. Based on the results of statistical analysis using one-way ANOVA, it was found that the calcium and iron content in the three commercial almond milk products showed significant differences. Conclusion: Almond milk has potential as an alternative to cow's milk, especially as a source of protein and calcium for individuals with special dietary needs.